Determination of the Plasticity Index of Soils with Fine-Grained Soils Using Methylene Blue Test - Ünver Otçu, Nermi̇n; Uzundurukan, Soner; Kaplan, Gökhan (Scientific Research Publishing, Inc., 2017)
The amount of fine material available in the soil is significant in Atterberg limits and methylene blue tests. In the context of Atterberg limits, increased amount of clay minerals contained in the soil increases liquid and plastic limit values; however, increasing sand content reduces the moisture content reducing the water retention capacity of the soil which in return reduces the plasticity index (PI) value. In the case of methylene blue test, which is used to specify the quality of the amount of fine material, existence of clay in the medium increases the pollution level of the sand and the amount of methylene solution (V1) used. In this study, soil classes were determined and pollution rates were identified with Atterberg limits, pycnometer, sieve analysis, hydrometer analysis and methylene blue tests conducted on 11 different natural soil samples collected from different regions. From the data obtained, first the relationship between PI and methylene blue (MB) was examined and was evaluated according to the results of the “single regression” method. Furthermore, the other coefficient of uniformity (Cu), coefficient of graduation (Cc), unit weight of soils (γs) parameters obtained from experimental studies were also subjected to “multiple regression analysis” in order to reveal their impact on the MB and this impact was confirmed taking both statistical analyses into account.
Keywords: 13. Climate action; 15. Life on land; 6. Clean water